Bioethical and legal aspects of abortion counseling under Chilean law - Undurraga Valdés, Verónica (Acta Bioethica, 2018)
The Chilean statute decriminalizing abortion under three specific grounds provides for a counseling program which guarantees patient’s autonomy. However, the reality is that not all counseling programs that are offered in Chile comply with this normative standard. The article analyzes abortion counseling from a legal and bioethical perspective, and examines the features of a counseling program respectful of the pregnant woman’s autonomy. The text concludes stating that the health care professional that offers support he/she should be involved in a respectful and genuine dialogue with the patient, provide adequate information, refraining from imposing his/her own interpretation about the experience of the woman, support her in deliberating and assume that her preferences and values must guide the process of decision making. The programs which do not fulfill these standards may be contravening legal obligations.